Proline Activity and Growth of Oil Palm affected by Aluminium Toxicity and Silica as Ameliorant - Annisa Khoiriyah; Eka Tarwaca Susila Putra; Prapto Yudono (Jurnal Ilmu Pertanian, 2016)
The research aims to investigate the effects of silica (Si) as an ameliorant on the proline compound concentration and the growth response of oil palm exposed to aluminum toxicity. The research was arranged in a complete randomized block design with 8 blocks as replications. The first factor was Al toxicity which consisted of two levels as without and with Al toxicity. Al toxicity treatment was applied by giving 300 ppm of Al concentrate along with watering activity regularly. The second factor was the application of silica which consisted of four levels as 0, 32, 64 g/plant. Proline and growth activities of leaf area, plant height, number of leaves, and dry weight were observed in the research. The data subjected to analysis of variance (ANOVA) at 5% test level. If the result of ANOVA showed significant differences among treatments, then the data would have been analyzed by Duncan’s Multiple Range Test (DMRT) at 5% test level. The results of the research provide information that Al toxicity increases proline compound in the plant tissues and decreases leaf area, plant height, number of leaves, and dry weight of Oil Palm. Applying Si at the level of 64 g/plant could increase proline concentrate and dry weight of oil palm exposed to A1 toxicity. Proline compound in the plant tissues did not have any correlation with the growth of oil palm. Thus, this case indicated that proline was a product and not a plant tolerant mechanism of Al toxicity.